2020
DOI: 10.1177/0260106020975247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 12 months of creatine supplementation and whole-body resistance training on measures of bone, muscle and strength in older males

Abstract: Background: The combination of creatine supplementation and resistance training (10–12 weeks) has been shown to increase bone mineral content and reduce a urinary indicator of bone resorption in older males compared with placebo. However, the longer-term effects (12 months) of creatine and resistance training on bone mineral density and bone geometric properties in older males is unknown. Aim: To assess the effects of 12 months of creatine supplementation and supervised, whole-body resistance training on bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 26 publications
(60 reference statements)
0
20
0
Order By: Relevance
“…When all studies were included in the analysis, higher-dose creatine supplementation daily, with and without a creatine-loading phase, had no greater effect on upper-body strength compared to the placebo. However, sensitivity analysis showed that when the Candow et al [27] study was removed, results became significant in favor of creatine. In this study, older males supplemented with higher-dose creatine daily during supervised, whole-body resistance training for 52 weeks.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…When all studies were included in the analysis, higher-dose creatine supplementation daily, with and without a creatine-loading phase, had no greater effect on upper-body strength compared to the placebo. However, sensitivity analysis showed that when the Candow et al [27] study was removed, results became significant in favor of creatine. In this study, older males supplemented with higher-dose creatine daily during supervised, whole-body resistance training for 52 weeks.…”
Section: Discussionmentioning
confidence: 98%
“…Previous meta-analyses have shown greater gains in measures of lean tissue mass (~1.2-1.3 kg) and strength from creatine supplementation and resistance training in older adults compared to the placebo [9,32,33]. Since the date of these publications, two additional studies [24,27] have been performed. When these studies were included in the current meta-analyses, creatine supplementation and resistance training still increased measures of lean tissue mass (~1.32 kg) and strength compared to the placebo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, excellent potential exists for creatine to support the health and function of older populations. Although nearly all of the original research on creatine used young, athletic populations, research in the past 10-15 years has highlighted creatine's ability to increase the ability to perform daily living activities, to delay fatigue, and to improve muscle mass in older populations [150][151][152][153][154][155][156][157][158].…”
Section: Other Considerationsmentioning
confidence: 99%